Comparison of kinesiotape, counterforce brace, and corticosteroid injection in patients with tennis elbow: A prospective, randomized, controlled study - Seyyed Mohammadreza Hoseini; Mohammad Taghipour; Rahmatollah Jokar; Mehrdad Mostafaloo; Hoda Shirafkan; Khodabakhsh Javanshir (PLoS ONE, 2025)
Objective The aim of the study was to compare the effects of corticosteroid injection, kinesio tape, and counterforce brace on pain intensity, Common Extensor Tendon thickness, grip strength, and functional status in the treatment of lateral epicondylitis. Design A total number of 51 patients were randomized into three groups. Group 1 was given kinesio tape, group 2 received a corticosteroid injection, and group 3 received a counterforce brace. Pain was measured using a visual analog scale, common extensor tendon thickness was measured with ultrasonography, functional status was measured using the disabilities of arm, shoulder, and hand questionnaire and grip strength was measured using a dynamometer. All evaluations were performed before treatment and at the second and fourth weeks after the treatment. Results No significant differences between the groups were observed for the visual analog scale scores, common extensor tendon thicknesses, grip strength, and disabilities of arm, shoulder, and hand questionnaire score compared to the baseline (P > 0.05). A statistically significant difference was found between the pretreatment and posttreatment evaluations of pain intensity and common extensor tendon thickness in all groups at the second and fourth weeks after treatment. According to the disabilities of arm, shoulder, and hand questionnaire scale, the condition improved significantly in the brace group and corticosteroid group, whereas it had not improved in the kinesiotaping group compared to before treatment. None of the treatment methods increased the patients’ grip strength (P > 0.05). Conclusion The corticosteroid injection, kinesiotape, and specially counterforce brace effectively reduced pain and tendon thickness. However, none of these treatment methods were superior to the others. Trial registration This study was registered in the Iranian Registry of Clinical Trials (IRCT20091214002851N7).